(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
In article presented for consideration are aspects of using “Stick Mobility” – innovate technology for improving the quality of movements in everyday life among all segments of the population among all segments of population. The stick training system is aimed at improving mobility, stability, and strength. The use of flexible sticks creates conditions for: restoring movement patterns, mobilizing joints, developing functional strength and neuromuscular control, and deep fascial stretching. Stick Mobility – is innovate technology which is becoming worldwide spread. System started in USA in 2015 and main goal is to help people reach their physical potential and improve their ability to move well. The system is accredited by: - National College of Physical Education (NCEP); - National Academy of Sports Medicine; - American Athletics and Fitness Association (AFAA); - National Strength Training Association (NSCA); - Alberta Fitness Leadership Certification Association. The innovative Stick Mobility technology is based on scientific principles, taking into account the biomechanics of movements and kinesiological approaches during specially organized classes. Among the list of other innovative sports and health technologies, it stands out for the following specific features:1) combines mobilization, stabilization and strength training, ensuring the comprehensive development of physical qualities;2) contributes to the optimization of the physical education process, increasing coordination abilities, balance and control of movements in a person of any age; 3) helps restore functional mobility and reduce the risk of re-injury; 4) high level of adaptability; 5) based on neuromuscular activation;6) interdisciplinary potential and prospects for application in educational programs, sports training, physical rehabilitation and fitness industry.